Cytotoxic effects of pesticide in somatic cells of Vicia faba L. - Pandey, R.M. (Інститут клітинної біології та генетичної інженерії НАН України, 2008)
The effects of pesticides (Endosulfan, Dieldrin, Aldrin) on cell division and chromosomal morphology of Vicia faba L. were studied. The results showed that the pesticides are mitodepressive in higher concentrations and mitopromotor in lower concentrations and induced a variety of chromosomal abnormalities such as stickiness, fragments, chromatid separation, disturbed metaphase, C-mitosis, laggards, precocious movement and late separation where lagging chromosomes were predominant. The concentration of 500 ppm or above, for all the pesticides used in the present study showed pronounced toxic effect. In remaining treatments, although the mitotic index was improved but less than that of absolute controls.